Forecasting of India VIX as a Measure of Sentiment - Banerjee, Arindam (International Journal of Economics and Financial Issues, 2019)
The India VIX represents the sentiment of traders in the Indian market, so by forecasting the future value of India VIX, we get a feel for investor sentiment in future. The objective of this study is to fit a forecasting model on India VIX using auto regressive integrated moving average (ARIMA). The model would be useful in having a glimpse of investor mood in near future. This is probably the first of its kind study based on Indian market. The motivation of this study lies not only on the pervasive agreement that the VIX is a barograph of the general marketplace sentiment as to what concerns investors’ risk appetite, but also on the fact that there are many trading strategies that depend on the VIX index for speculative and hedging determinations. The study found ARIMA (1-0-2) forecasting model on VIX produces better forecasting result. We also validated the model with an out-of-sample dataset and found the model reliable. Keywords: VIX, India, Sentiment, Forecasting, ARIMA JEL Classifications: C53, G17 DOI: https://doi.org/10.32479/ijefi.8046